Caring for adults with CHD in the era of coronavirus disease 2019 pandemic: early experience in an Italian tertiary centre. (6th October 2020) - Scognamiglio, Giancarlo; Fusco, Flavia; Merola, Assunta; Palma, Michela; Correra, Anna; Sarubbi, Berardo
Abstract: Background: Adults with CHD are known to greatly benefit from a prompt access to continuous expert care. On the other hand, coronavirus disease 2019 pandemic has determined a dramatic worldwide reconfiguration of the healthcare systems, with rapid redeployment of resources towards this emergency. Italy was the first Western country affected by a large-scale spread of coronavirus disease 2019. The aim of our study is to analyse the impact of the coronavirus disease 2019 outbreak on in-hospital care of patients with CHD in an Italian tertiary centre. Methods and results: We retrospectively reviewed data on CHD hospital admissions in our centre since 1 March, 2020, when the adoption of a strict infection containment policy throughout the country resulted in limited access of patients to routine hospital care and resources reallocation to the care of infected patients. Comparison with data from the previous year was performed in order to identify any relevant differences attributable to the outbreak. Despite cancellation of all elective procedures, the overall number of urgent hospital admission remained stable throughout the period of study. Patients admitted during the pandemic had greater disease complexity (p = 0.001) with longer length of in-hospital stay (p = 0.01). No adverse events or positive swabs were reported among CHD patients who were admitted to hospital or medical personnel caring for these patients. Conclusion: Data from our early experience suggest that coronavirus disease 2019 pandemic did not impact significantly on the provision of urgent care to adult patients with CHD.